mRNA-based SARS-CoV-2 Comirnaty vaccine elicits weak and short specific memory B cell response in individuals with no previous infection - Casado, José L.; Vizcarra, Pilar; Martín-Hondarza, Adrián; Gómez-Maldonado, Sandra; Muedra-Sánchez, Magdalena; del Pino, Judith; Mirabella, Itria G.; Martín-Colmenarejo, Sara; Haemmerle, Johannes; Fernández-Escribano, Marina; Vallejo, Alejandro (Frontiers in Immunology, 2023)
Objectives: The dynamics of the memory B cell (MBC) repertoire after SARS-CoV-2 vaccination is crucial for assessing long-term immunity. We compare spike-specific MBC responses between SARS-CoV-2 unexposed and recovered individuals and their impact on breakthrough infections during follow-up. Methods: Spike-specific MBC and T cells were quantified at inclusion and after two doses of mRNA vaccine in a longitudinal cohort of 85 naïve and 64 recovered participants (47 with positive serology and 17 with negative serology after infection). Results: At inclusion, there was minimal spike-specific MBC in naïve SARS-CoV-2 individuals. After the second vaccine dose, MBCs were significantly boosted in naïve individuals but reached a significantly lower level than that observed even in unvaccinated SARS-CoV-2 convalescents (p<0.001). Furthermore, while the secondary memory B cell (MBC) population consisted of 100%, 33%, and 76% IgG+, IgM+, and IgA+ expressing cells, respectively, in the unexposed group, the MBC response showed a significant decrease across all isotypes. Similarly, although secondary specific IgG+, IgM+, and IgA+-MBC isotypes were found in 100%, 39%, and 76% of the unexposed participants, respectively, the magnitude of the MBC levels was significantly lower for all the isotypes compared to convalescents. Interestingly, convalescents without an initial serological response had a lower MBC response, like what found in unexposed subjects. There was an inverse correlation between specific MBCs (r=-0.307; p=0.027), especially for isotype IgA+ (r=-0.279, p=0.045), and the time since the second vaccination dose. Furthermore, during a median follow-up of 434 days (IQR, 339-495), 49 out of 149 individuals (33%) became infected, 29 in naïve and 20 in convalescent individuals, showing a significant correlation between spike-specific MBC magnitude after vaccination and the time for SARS-CoV-2 infection, especially for IgA+/IgG+ MBC isotypes. Conclusions: MBCs were primed by mRNA-based vaccination in most cases, but SARS-CoV-2 naïve individuals had a blunted specific MBC response, and this was associated with a shorter time to breakthrough SARS-CoV-2 infection.